(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The speed of warehouse order processing is a key industry imperative for customer satisfaction. One way warehouse managers can achieve this is by comprehensively optimizing warehouse operations. Several researchers have observed that warehouse order processing activities contribute a significant portion of warehouse time and total costs. This study used the packaging materials warehouse of a chemical company in Tangerang City, Indonesia. The main problems identified in this study included long picking times, the risk of component picking errors, and low stock visibility. Several methodologies were used to address these issues. The process began with mapping SKUs based on service frequency and quantity (fast-moving/slow-moving). Based on the collected data, changes were made to the item layout. Furthermore, additional areas for packaging support components, such as lids, were added near the packaging to reduce errors during picking. Furthermore, 5S practices were implemented to remove unused items from the packaging warehouse. This also helped the warehouse expand its storage space. The results showed a 50% reduction in picking time, from the initial standard time of 4 seconds per item to 2 seconds per item. Several unsafe storage areas were also removed, improving operator safety during picking and contributing to increased warehouse capacity. Furthermore, the implementation of a pail storage system also facilitated faster receipt and service of goods. The incidence of damaged pails during storage was also reduced. The results of this study concluded that the 5S method and determining the layout based on the movement of goods in the warehouse can have a significant impact on warehouse productivity.